Debunking the Maternal Myths and Re-Interpreting Motherhood - Thapa, Bibeka (Chaturbhujeshwar Academic Journal, 2023)
This paper interprets the fundamentals of motherhood with a particular emphasis on matricentric feminist viewpoints. It delves deeply into the complex aspects of motherhood, shedding light on its intricate structure with the help of feminist perspectives. Through a critical analysis of various viewpoints, the paper reveals how gender roles, cultural norms, and power dynamics interact to shape how mothers perceive and experience motherhood. It references the challenges mothers face in patriarchal systems and draws from the works of prominent feminist researchers. It also highlights how feminist ideas provide an alternative perspective for examining prevalent stereotypes and challenging binary notions of motherhood. Through this, the study contributes to a deeper understanding of how feminist viewpoints influence conceptions of motherhood and reshape the discourse on women's roles and identities. The abstract underscores the importance of considering social roles and gender issues in this investigation, highlighting their pivotal roles in shaping mothers' experiences in society.